Pozycja konkurencyjna gmin w oparciu o udział dochodów budżetowych we wpływach w podatku dochodowym - Sobczyk, Andrzej (The Competitive Position of Communes Based on the Budget Income within the Returns of the Income Tax, 2009)
The article is theoretical-practical in character. The issue of creating the competitive position by a commune has been presented as well as the differentiation of the returns into the communal budget from the participation in the income taxes, subject to the enterprise tax form and the location of the activity
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 299-305